Analisis Hukum Terhadap Rencana Pembuangan Limbah Nuklir ke Laut Pasca Terjadinya Gempa Bumi dan Tsunami di Jepang - Aprilia Mawaddah; Maria Maya Lestari; Ledy Diana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Explanation of the Convention On Nuclear Safety 1994 Article 16 Number 1, 2 and 3 that States that have or will build Nuclear Power Plants (NPPs) in their territory must take appropriate measures related to facilities, security, emergency plans carried out in the event of an emergency in the vicinity of the NPP. Construction of Fukushima NPP The existing nuclear reactor at the nuclear plant was built with insufficient power to withstand the Earthquake and Tsunami that occurred in Japan on March 11, 2011 causing explosions and leaks in 4 nuclear reactors. Japan announced that tanks used to hold waste from leaking nuclear reactors could no longer hold it, so the waste had to be dumped into the sea. The main problem in this study is about the regulation of International Law violated by Japan based on its decision to dump nuclear waste into the Sea, and how the impact will be on the environment. The type of research used in this study is normative legal research or can also be called doctrinal legal research. Normative legal research is literature law research. The action that will be taken by Japan who want to dispose of nuclear waste that they have stored for years due to the Earthquake and Tsunami event has received a lot of resistance from various elements. Especially from the Japanese people themselves to protests from neighboring countries who are afraid that they will also be affected by the waste if it is thrown into the sea. It is hoped that Japan can take appropriate action before doing so because it will not only harm its country but also harm other countries that are disappointed with the actions that Japan will take.